2(x) - [12 + 2y) ➡ 0
2(x - y - 6)
2 ➡0 {It doesn't have any solution for the equation}
x - y - 6 ➡0
y ➡ 6 over -1 ; x ➡6 over 1
The slope = 1
Therefore your answer would have to be ➡
y= 6 over -1 ; x = 6 over 1 ; slope = 1
Answer:
(x) = √ x + 4
Step-by-step explanation:
step 1) replace f(x) with y
y = x² - 4
step 2) switch the x and y (because every (x, y) has a (y, x))
x = y² - 4
step 3) add 4 to both sides of the equal sign
x + 4 = y²
step 4) take the square root of both sides of the equal sign (the square root symbol cancels out the ²)
√ x + 4 = y
step 5) you know have the inverse of f(x) = x² - 4
(x) = √ x + 4
Answer:
6/25
Step-by-step explanation:
Answer:
-4x<16 the sign flips if you divide by a negative
Step-by-step explanation:
4x<-16
x<-4
but
-4x<16
x>-4